Histopathological alterations in the prostates of Mongolian gerbils exposed to a high-fat diet and di-n-butyl phthalate individually or in combination - Jesus, Mariana Marcielo de; Negrin, Ana Carolina; Taboga, Sebastiao Roberto [UNESP]; Pinto-Fochi, Maria Etelvina [UNESP]; Goes, Rejane Maira [UNESP] (Elsevier B.V., 2015)
Both high-fat diet and exposure to endocrine-disrupting chemicals have been implicated in susceptibility to pathological prostate lesions, but the consequences of combining the two have not yet been examined. We evaluated the effects of gestational and postnatal exposure to a high-fat diet (20% fat) and low doses of di-n-butyl phthalate (DBP; 5 mg/kg/day), individually or in combination, on the tissue response and incidence of pathological lesions in the ventral prostate of adult gerbils. Continuous intake of a high-fat diet caused dyslipidemia, hypertrophy, and promoted the development of inflammatory, premalignant and malignant prostate lesions, even in the absence of obesity. Life-time DBP exposure was obesogenic and dyslipidemic and increased the incidence of premalignant prostate lesions. Combined exposure to DBP and a high-fat diet also caused prostate hypertrophy, but the effects were less severe than those of individual treatments; combined exposure neither induced an inflammatory response nor altered serum lipid content. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Prostate; Mongolian gerbil; High-fat diet; Di-n-butyl phthalate; Histopathological lesions; Inflammatory disorders; Prostatic intraepithelial neoplasia; Microinvasive carcinoma